Guidelines of the Polish Psychiatric Association – Wroclaw Division, the Polish Society of Family Medicine and the College of Family Physicians in Poland for diagnosis and treatment of depressive disorders in primary health care - Piotrowski, Patryk; Gondek, Tomasz Maciej; Rymaszewska, Joanna; Beszłej, Jan Aleksander; Czachowski, Sławomir; Parmentier, Henk; Kurpas, Donata (Family Medicine & Primary Care Review, 2017)
Mental disorders are common among patients seen by primary care physicians. T he most common ones are: mood disorders, anxiety disorders and somatic disorders. Psychological problems often coexist with somatic illnesses, negatively affecting their natural course, adherence to medicines and treatment, and thus the effectiveness of treatment. A part from biological determinants, such as genetic load, somatic disease burden and treatment options, depressive disorders are also linked to socio-demographic factors. The multitude of issues that require attention from the physician during routine medical consultations makes it difficult to diagnose and decide on appropriate treatment. Screening tools with proven psychometric parameters can facilitate this process. Most patients with unipolar mood disorders can be treated within the primary care setting. They are seeking help from their well-known family physicians and often do not require a psychiatric consultation. I t should be emphasized that the vast majority of primary care patients report symptoms of psychosomatic disorders that are aggravated by daily stressful situations. Before starting diagnostic and therapeutic actions, it is advisable to extend the consultation time, analyze their family, financial and professional situation and convince them to use stress management techniques, as well as to persuade them to change perception of the environment and avoid negative habits in life and nutrition. I f there is no improvement of the depressive symptoms after 2 to 4 weeks, other therapeutic strategies should be considered. I n this paper, the authors propose simplified regimens and indicate the possibilities and limitations of the treatment of mental health disorders in the primary health care setting.